The Use of AI Tools in Supporting Academic Activities for High School/Vocational School Teachers in Bekasi - Herianto S.Pd., MT; Bagus Tri Mahardika; Suzuki Syofian; Yan Sofyan Andhana Saputra; Darsono (JEPTIRA, 2025)
The goal of this community service project was to improve lecturers' and teachers' abilities to use cutting-edge prompting strategies based on artificial intelligence (AI) as a breakthrough in teaching. Chain of Thought (CoT) and Role Prompting, two crucial prompting techniques that have been demonstrated to greatly enhance human-AI interaction in educational settings, were the main topics of the course. Twenty-five participants from different educational institutions participated in a series of workshops, practical exercises, and case-based discussions. The findings showed that participants' capacity to create efficient and contextually relevant prompts had significantly improved. Additionally, the training helped teachers become more technologically literate and acted as a link to assist the continuous digital transformation of education. The initiative highlights the importance of equipping educators with AI-related skills that are both practical and pedagogically meaningful, especially as generative technologies become increasingly embedded in learning environments.